2006
DOI: 10.1111/j.1399-302x.2005.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine pattern determines the progression of experimental periodontal disease induced by Actinobacillus actinomycetemcomitans through the modulation of MMPs, RANKL, and their physiological inhibitors

Abstract: It is possible that the pattern of cytokines produced in periodontal tissues determines the progression and the severity of experimental periodontal disease, controlling the breakdown of soft and bone tissues through the balance between MMPs/TIMP and RANKL/OPG expression in gingival tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
214
1
59

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(285 citation statements)
references
References 53 publications
11
214
1
59
Order By: Relevance
“…Furthermore, the increased ePD severity correlates with the significant increase in the levels of RANKL and MMP-13, and with the increase of RANKL/OPG and MMP-13/TIMPs ratios, characteristically associated with periodontal destruction. 13,19,45 Looking for the reason of the altered adaptive response because of RA/ PD interaction, we found that the submandibular LNs (the major draining LNs of oral cavity), which are significantly enlarged by the ePD induction, presented an even higher enlargement because of the pristane injection (data not shown), being an indicative of systemic immune reactivity to the PIA. Furthermore, the pattern of the transcription factors responsible for T-cell polarization expressed in submandibular LN was modulated by the PIA, the levels of Tbet and RORg being significantly increased in AIRmax mice submitted to both PIA and ePD protocols.…”
Section: Experimental Periodontitis and Arthritis Interaction Ap Trommentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the increased ePD severity correlates with the significant increase in the levels of RANKL and MMP-13, and with the increase of RANKL/OPG and MMP-13/TIMPs ratios, characteristically associated with periodontal destruction. 13,19,45 Looking for the reason of the altered adaptive response because of RA/ PD interaction, we found that the submandibular LNs (the major draining LNs of oral cavity), which are significantly enlarged by the ePD induction, presented an even higher enlargement because of the pristane injection (data not shown), being an indicative of systemic immune reactivity to the PIA. Furthermore, the pattern of the transcription factors responsible for T-cell polarization expressed in submandibular LN was modulated by the PIA, the levels of Tbet and RORg being significantly increased in AIRmax mice submitted to both PIA and ePD protocols.…”
Section: Experimental Periodontitis and Arthritis Interaction Ap Trommentioning
confidence: 92%
“…10,13 Furthermore, in both diseases, these cytokines present a catabolic function over the periodontal tissues, mediated by the production of matrix metalloproteinases (MMPs) and the osteoclastogenic factor RANKL. 10,[13][14][15][16][17][18][19][20] On the other hand, Th2-and anti-inflammatory cytokines such as IL-4 and IL-10 exert the reverse effect, mediating the direct downregulation of inflammatory cytokines and their signaling pathways, and also upregulating the expression of TIMPs and OPG, the endogenous inhibitors of MMPs and RANKL, respectively. 10,13,19,21,22 However, a major unanswered question is how a joint lesion could influence the host response at periodontal environment to affect PD outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Mice with A. actinomycetemcomitans-induced periodontitis demonstrated upregulation of Th1 cytokines (IFN-γ and IL-12) in the early stage and that of Th2 cytokines (IL-4 and IL-10) in the late stage, indicating the involvement of each T cell subset in different disease stages [9]. Destructive effects of Th1 and Th2 cytokines were suggested in an experiment that showed that IFN-γ-and IL-6-deficient mice were resistant to P. gingivalis-induced alveolar bone loss [7].…”
Section: Cd4mentioning
confidence: 99%
“…Also, genetic factors have an important role on the balance between protective and destructive chemical mediators [17,18]. Genetic components may determine the roles of the immune system, host response, and cytokines in periodontal disease [19].…”
Section: Periodontitismentioning
confidence: 99%